POPULATION GROWTH FOR Daphnia magna OF MEDIA BANANA STEM, CABBAGE, AND WATER HYACINTH WITH DIFFERENT STOCKING DENSITY - Risma Putri TM; Nuraini Nuraini; Sukendi Sukendi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
Abtrak  This research was conducted on August until September 2018 at Fish Hatchery and Breeding Laboratory, Fisheries and Marine Science Faculty, Riau University. The purpose of this research to determine the population of Daphnia magna were cultured on different media and stocking density that generates the highest population. This research method used is an experimental method. The experimental design used was completely randomized design (CRD) with factorial design 2 factors which consisted of factors A: Media different that Banana Stem 12 g/l, Cabbage12 g/l, Water Hyacinth 12 g/l and factor B: Solid different initial stocking 100 ind/l and 200 ind/l as many as 6 treatments, 3 repetitions so obtained 18 experimental units. Media and stocking density is real (P<0,05) effect on the population Daphnia magna. The best treatment of Daphnia magna population during the 24 day study period generated by treatment of KP2 (Cabbage 12g/l+ Stocking Density 200 ind/l) with an average value of 283. While the lowest for the treatment population BPP1 (Banana Stem 12 g/l +Stocking Density 100 ind/l) with an overall average of 111 ind/l. Based on the results of observations of phytoplankton abundance in each treatment the highest was KP2 (Cabbage 12 g / L + stocking density 200 Ind/l) with a total of 6,934,738 ind/ l while the lowest was BPP1 (Banana stem 12 g / L + 100 stocking density ind/l) 2,147,532 ind/l. Water quality during the study showed a good range for growth of Daphnia magna is Temperatures range between 24,0- 30,10C °C, and pH ranging from 7, 2 - 8,1.  Keywords : Media, Stocking density, Population, Daphnia magna